Hydrophobic antibacterial particle, preparation method thereof and application of hydrophobic antibacterial particle in real stone paint

Modify nano-zinc through the wormwood extraction solution and silane coupling agent, and reproduce the polystumin lotion and sodium alginate-mesee solution of polylerate, forming a hydrophobic dredging with excellent antibacterial, hydrophobicity and persistent hydrophobic. Antibacterial particles solve the problem of nano -zinc oxide antibacterial properties and persistence in existing technologies, and are suitable for the functional coating field of real stone paint.

CN119350906AActive Publication Date: 2025-01-24SHANGHAI UNIV OF ENG SCI

Patent Information

Application Number
CN202411720126.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-24
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The antibacterial properties and durability of nano zinc oxide in existing antibacterial coatings are insufficient, and their dispersion in the coatings are poor, which affects the hydrophobicity and antibacterial properties of the coatings.

Method used

The zinc oxide was modified by the wormwood extraction solution and the siralr coupling agent to form a wormwood-puppet-to-nano-nanoxyboxide, and it modified it with polyraithic acid polychen lotion and sodium alginate-melted solution. Match, form a spherical particle, and then react with calcium chloride to prepare a hydrophobic antibacterial particles with excellent antibacterial, hydrophobic and durable.

Benefits of technology

The hydrophobic antibacterial particles used in real stone paint have excellent antibacterial, hydrophobic and antibacterial durability. It is suitable for functional coating fields, and the preparation method is economical and practical, suitable for large -scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350906A_ABST
    Figure CN119350906A_ABST
Patent Text Reader

Abstract

The invention discloses hydrophobic antibacterial particles as well as a preparation method and application thereof in real stone paint. The preparation method of the hydrophobic antibacterial particles comprises the following steps: firstly, compounding a polylysine modified polyurea emulsion with a sodium alginate-gelatin solution to obtain a composite emulsion, then wrapping the composite emulsion with wormwood-coupling modified nano zinc oxide to form spherical particles, and finally, carrying out a cross-linking reaction on the spherical particles and calcium chloride to obtain the hydrophobic antibacterial particles. The wormwood-coupling modified zinc oxide nanoparticles are obtained by sequentially modifying zinc oxide with a wormwood extracting solution and a silane coupling agent. The hydrophobic antibacterial particles provided by the invention have excellent antibacterial property, hydrophobicity and antibacterial durability, and the hydrophobic antibacterial particles are added into the stone-like paint, so that the prepared stone-like paint containing the hydrophobic antibacterial particles not only has excellent antibacterial property, hydrophobicity and antibacterial durability, but also has relatively low illumination requirements on the environment; good antibacterial performance is achieved in visible light and dark environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to hydrophobic antibacterial particles and a preparation method thereof and application of the hydrophobic antibacterial particles in real stone paint, belonging to the technical field of functional coatings. Background Art

[0002] Real stone paint is a kind of paint with decorative effect similar to marble and granite, which is mainly made of natural stone powder of various colors. Buildings decorated with real stone paint have natural and real natural color, giving people a sense of elegance, harmony and solemnity, and are suitable for indoor and outdoor decoration of various buildings.

[0003] With the development of coating functionality, especially bacterial infection, people are paying more and more attention to antibacterial functional coatings. Dense public places are high-risk areas for bacterial cross-infection, and the growth and reproduction of bacteria on the surface of buildings is the source of people's illness. The erosion and damage of microorganisms on the coating surface has led to the shortening of the service life of the material and the existence of safety hazards, which has always been a potential threat to our daily life. Therefore, the requirements for the antibacterial properties of real stone paint are getting higher and higher.

[0004] At present, antibacterial coatings mainly achieve their antibacterial function by adding antibacterial agents. Antibacterial agents in coatings are mainly divided into organic antibacterial agents and inorganic antibacterial agents. Among them, organic antibacterial agents are easy to decompose, some organic antibacterial agents are harmful to the environment and have poor durability.

[0005] Inorganic antimicrobial agents are mainly divided into two categories. One is a metal ion antimicrobial agent that loads antimicrobial metal ions such as silver ions, copper ions, and zinc ions on an inorganic carrier. The other is a photocatalytic inorganic antimicrobial agent that uses semiconductor materials such as titanium dioxide as the main component to achieve antibacterial properties through its photocatalytic activity. Although the former has a significant antibacterial effect on the surface, its durability is poor. The latter has high requirements for environmental light and requires a specific environment to have good bactericidal ability. After being added to the coating, the prepared coating cannot meet the antibacterial requirements well.

[0006] Nano zinc oxide is an n-type semiconductor material, mainly including several structures such as hexagonal wurtzite phase, sphalerite, cesium chloride and salt rock. Nano zinc oxide is a non-toxic and biocompatible material, which is widely used in the cosmetics industry, textile industry, drug delivery, medicine and biomedicine.

[0007] In addition to being UV resistant, nano zinc oxide also has the ability to inhibit the growth of pathogens. It is currently often used as an antibacterial filler to prepare antibacterial coatings. For example, in the literature (Preparation of Nano Zinc Oxide / Styrene-Acrylic Emulsion Interior Wall Paint, Journal of Hanshan Normal College, Cai Hong, Qiu Heyuan, Vol. 27, No. 6), nano zinc oxide was added to styrene-acrylic emulsion paint to prepare an interior wall paint with antibacterial properties.

[0008] Although nano zinc oxide has excellent performance, it still has certain defects when used in antibacterial coatings: 1) Although nano zinc oxide has the ability to inhibit the growth of pathogens, its antibacterial performance and antibacterial durability are not strong enough, and it cannot meet people's high demand for antibacterial properties of coatings; 2) Generally speaking, if the coating surface formed by the coating is hydrophobic, it can effectively prevent the attachment of microorganisms, thereby making the coating antibacterial. However, the current nano zinc oxide is not only easy to agglomerate, but also has poor compatibility with the polymer resin in the coating, cannot be evenly dispersed in the resin, and has poor hydrophobicity. After being added to the coating, it cannot make the coating surface have good hydrophobic properties, affecting the antibacterial properties of the coating; 3) Like nano titanium dioxide, nano zinc oxide has a high demand for environmental light and can usually only stimulate active oxygen for antibacterial effects under ultraviolet conditions, which affects the antibacterial properties of the coating.

[0009] In response to the above defects, researchers have adopted a series of physical and chemical methods to modify and modify nano zinc oxide so that it can be better used in coatings. For example: In the literature (Research on Antibacterial Modification of Nano Zinc Oxide Particles and Their Application in Photocurable Coatings, Beijing University of Chemical Technology, Tang Nannan), silane coupling agents were used to modify tetragonal needle-shaped and rod-shaped nano zinc oxides, and the modified nano zinc oxides were used as additives to prepare UV-curable antibacterial coatings; in the literature (Research on Triazole Ring-Based Fluorinated Aromatic Hydrocarbon-Modified Nano Zinc Oxide and Its Application in Marine Antifouling Coatings, Hainan University, Yang Yu), triazole ring-based fluorinated aromatic hydrocarbons were used to modify nano zinc oxide, and the modified nano zinc oxide was used as an additive to prepare UV-curable antibacterial coatings. It is used as an additive to prepare marine antifouling coatings; the literature (Green synthesis of nano zinc oxide from Sophora japonica extract and its antibacterial activity, New Chemical Materials, Cheng Zhong, Tang Shanwen, Wu Yu, Wang Juan, Vol. 50, No. 11) uses Sophora japonica extract to modify nano zinc oxide, and the antibacterial activity of the modified nano zinc oxide is tested; Patent CN200910198971.0 uses zinc oxide modification additives to modify nano zinc oxide particles, and the modified nano zinc oxide is used as a filler to prepare nano zinc oxide antibacterial and antifouling coatings.

[0010] The currently disclosed modification methods of nano zinc oxide, although they can modify nano zinc oxide, can only modify one aspect of the performance of nano zinc oxide, such as antibacterial property and hydrophobicity, and cannot simultaneously modify the antibacterial property, hydrophobicity and durability of nano zinc oxide in an all-round way. When the modified nano zinc oxide is used as a filler for preparing functional coatings (including functional real stone paint), the prepared coatings cannot meet the functional requirements well. Summary of the invention

[0011] In view of the above problems existing in the prior art, the object of the present invention is to provide a hydrophobic antibacterial particle and a preparation method thereof and application thereof in real stone paint.

[0012] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0013] A hydrophobic antibacterial particle is prepared by first compounding a polylysine-modified polyurea emulsion with a sodium alginate-gelatin solution to obtain a composite emulsion, then encapsulating the composite emulsion with wormwood-coupled modified nano zinc oxide to form spherical particles, and then cross-linking the spherical particles with calcium chloride; the wormwood-coupled modified nano zinc oxide is obtained by sequentially modifying zinc oxide with wormwood extract and a silane coupling agent.

[0014] A method for preparing the hydrophobic antibacterial particles of the present invention comprises the following steps:

[0015] a) dissolving zinc acetate dihydrate in deionized water, then dropping ammonia water and wormwood extract therein, stirring at room temperature for 3 to 5 hours (stirring speed is 250 to 500 rpm), collecting the solid product, and obtaining wormwood-modified nano zinc oxide;

[0016] b) dispersing the wormwood-modified nano zinc oxide in ethanol, then adding a silane coupling agent and deionized water thereto, stirring the resulting mixture at 75 to 85° C. for 1 to 3 hours (stirring speed of 300 to 500 rpm), collecting the solid product, and obtaining wormwood-coupled modified nano zinc oxide;

[0017] c) adding isocyanate to a reactor, adding polyetheramine dropwise at 40-45°C, and reacting with stirring at a temperature of 2-2.5 hours (stirring speed of 180-220rpm); then heating to 80-85°C, adding a hydrophilic chain extender, and reacting with stirring at a temperature of 1-1.5 hours; then keeping the temperature at 80-85°C unchanged, adding polylysine, and reacting with stirring at a temperature of 1-1.5 hours; then cooling to 70-75°C, adding a crosslinking agent, and reacting with stirring at a temperature of 0.5-1 hour; continuing to cool to 45-50°C, adding a neutralizing agent, and reacting with stirring at a temperature of 15-30 minutes; finally cooling to 30-35°C, adding deionized water dropwise, and reacting with stirring at a temperature of 0.5-1.5 hours (stirring speed of 450-700rpm), to obtain a polylysine-modified polyurea emulsion;

[0018] d) adding equal amounts of sodium alginate and gelatin into deionized water, and stirring the mixture at 60 to 70° C. for 5 to 6 hours to obtain a sodium alginate-gelatin solution;

[0019] e) mixing the polylysine-modified polyurea emulsion of step c) and the sodium alginate-gelatin solution of step d) at room temperature to obtain a composite emulsion;

[0020] f) adding the composite emulsion evenly to the surface of the wormwood-coupled modified nano zinc oxide, shaking evenly to allow the composite emulsion to be wrapped by the wormwood-coupled modified nano zinc oxide to form spherical particles, adding the spherical particles to an aqueous solution of calcium chloride, and subjecting the resulting mixture to a cross-linking reaction at room temperature for 1 to 3 hours, terminating the reaction, and freeze-drying the resulting reactant under vacuum to a constant weight (freezing temperature of -20 to -40°C, freezing time of 24 to 72 hours), thereby obtaining the hydrophobic antibacterial particles.

[0021] In one embodiment, in step a), the preparation of the wormwood extract comprises the following operations:

[0022] The dried mugwort is soaked in a 60-70wt% ethanol aqueous solution at a temperature of 60-70°C for 30-60 minutes. After the soaking, it is filtered to obtain the filtrate, which is the mugwort extract.

[0023] In a preferred embodiment, during the preparation of the mugwort extract, the added amounts of dry mugwort and 60-70wt% ethanol aqueous solution are: 5-10 parts by mass of dry mugwort and 40-90 parts by mass of 60-70wt% ethanol aqueous solution.

[0024] In one embodiment, in step a), the added amounts of zinc acetate dihydrate, deionized water, ammonia water, and wormwood leaf extract are: 4 to 9 parts by mass of zinc acetate dihydrate, 20 to 40 parts by mass of deionized water, 2 to 5 parts by mass of ammonia water, and 1 to 10 parts by mass of wormwood leaf extract.

[0025] In one embodiment, in step a), the operation of collecting the solid product is as follows:

[0026] After the reaction is completed, the reaction solution is vacuum filtered, and the obtained filter cake is washed with anhydrous ethanol and deionized water respectively, and then dried at 80-125° C. for 7-12 hours to obtain the wormwood-modified nano zinc oxide.

[0027] In one embodiment, in step b), the silane coupling agent is any one of KH570, KH550, and KH560.

[0028] In one implementation scheme, in step b), the added amounts of wormwood-modified nano zinc oxide, ethanol, silane coupling agent, and deionized water are: 1 to 2 parts by mass of wormwood-modified nano zinc oxide, 30 to 60 parts by mass of ethanol, 5 to 20 parts by mass of silane coupling agent, and 10 to 20 parts by mass of deionized water.

[0029] In one embodiment, in step b), the operation of collecting the solid product is as follows:

[0030] After the reaction is completed, the reaction solution is cooled to room temperature and then centrifuged. The separated precipitate is washed and filtered with ethanol. The filtered product is dried at 70 to 80° C. for 8 to 12 hours to obtain the wormwood-coupled modified nano zinc oxide.

[0031] In one embodiment, in step c), the added amounts of isocyanate, polyetheramine, hydrophilic chain extender, polylysine, crosslinking agent, neutralizer, and deionized water are as follows: 3.5 to 7 parts by mass of isocyanate, 10.5 to 21 parts by mass of polyetheramine, 0.28 to 0.56 parts by mass of hydrophilic chain extender, 0.1 to 0.28 parts by mass of polylysine, 0.14 to 0.28 parts by mass of crosslinking agent, 0.38 to 0.4 parts by mass of neutralizer, and 20 to 40 parts by mass of deionized water.

[0032] In one embodiment, in step c), the isocyanate is any one of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, polymethylene polyphenyl polyisocyanate, and hexamethylene diisocyanate; the polyetheramine is any one of polyetheramine D2000, polyetheramine ED900, and polyetheramine D230; the hydrophilic chain extender is any one of 2,2-bis(hydroxymethyl)butyric acid, dihydroxymethylpropionic acid, and dihydroxysulfonate; the polylysine is any one of ε-polylysine and α-polylysine; the cross-linking agent is any one of trimethylolpropane, 1,2-propylene glycol, and ethylene glycol; and the neutralizer is any one of triethylamine, dimethylethanolamine, and ammonia water.

[0033] In one embodiment, in step d), the mass concentration of the obtained sodium alginate-gelatin solution is 2% to 6%.

[0034] In one embodiment, in step e), the amounts of polylysine-modified polyurea emulsion and sodium alginate-gelatin solution added to the composite emulsion are: 0.09 to 0.12 parts by mass of polylysine-modified polyurea emulsion and 15 to 20 parts by mass of sodium alginate-gelatin solution.

[0035] In one implementation scheme, in step f), the added amounts of wormwood-coupled modified nano zinc oxide and calcium chloride aqueous solution are: 0.2-0.4 parts by mass of wormwood-coupled modified nano zinc oxide and 20-40 parts by mass of calcium chloride aqueous solution, wherein the mass concentration of the calcium chloride aqueous solution is 2.5-5%.

[0036] In one embodiment, in step f), the composite emulsion is uniformly sprayed onto the surface of the wormwood-coupled modified nano zinc oxide in a uniform spraying manner at a spraying speed of 2 to 200 ml / min.

[0037] A hydrophobic antibacterial particle-containing real stone paint prepared by using the hydrophobic antibacterial particles of the present invention, wherein the hydrophobic antibacterial particle-containing real stone paint has the following composition and proportion:

[0038] Resin: 10-30 parts by mass;

[0039] Colored sand: 50-70 parts by weight;

[0040] Hydrophobic antibacterial particles: 0.1 to 5 parts by weight;

[0041] Titanium dioxide: 5-15 parts by mass;

[0042] Thickener: 0.2-0.5 parts by mass;

[0043] Defoaming agent: 0.1-0.3 parts by mass;

[0044] Wetting and dispersing agent: 0.2-0.6 parts by mass;

[0045] Film-forming aid: 0.2-0.5 parts by weight.

[0046] In one embodiment, the resin is at least one of pure acrylic resin, silicone acrylic resin, styrene acrylic resin, and acetate acrylic resin.

[0047] In one embodiment, the titanium dioxide is any one of rutile titanium dioxide and anatase titanium dioxide.

[0048] In one embodiment, the thickener is any one or two of hydroxyethyl cellulose ether, polyacrylate, polyurethane thickener, and associative alkali swelling thickener.

[0049] In one embodiment, the defoaming agent is at least one of mineral oils, silicones (such as Dow Corning DC-62), and polyethers (such as polyether siloxane, polyethylene glycol, etc.).

[0050] In one embodiment, the wetting and dispersing agent is at least one of acrylic acid, alkylhydroxy ammonium salt (such as BYK-180), high molecular weight carboxylic acid, and modified polysiloxane.

[0051] In one embodiment, the film-forming aid is at least one of alcohols (such as propylene glycol, ethylene glycol, etc.), alcohol esters (such as dodecyl alcohol ester), and alcohol ethers (such as propylene glycol methyl ether PM, propylene glycol ethyl ether, propylene glycol butyl ether, etc.).

[0052] A method for preparing the real stone paint containing hydrophobic antibacterial particles comprises the following steps: under stirring, sequentially adding proportions of colored sand, hydrophobic antibacterial particles, titanium dioxide, thickener, defoamer, wetting dispersant and film-forming aid to a proportion of resin, stirring and mixing evenly to obtain the real stone paint containing hydrophobic antibacterial particles.

[0053] Compared with the prior art, the present invention has the following significant beneficial effects:

[0054] The invention firstly sequentially uses wormwood extract and silane coupling agent to modify zinc oxide, compound polylysine modified polyurea emulsion and sodium alginate-gelatin solution to obtain composite emulsion, then wraps the composite emulsion with wormwood-coupled modified nano zinc oxide to form spherical particles, then cross-links the spherical particles with calcium chloride to obtain hydrophobic antibacterial particles with excellent antibacterial property, hydrophobicity and antibacterial persistence, and adds the hydrophobic antibacterial particles into real stone paint, so that the prepared real stone paint containing hydrophobic antibacterial particles not only has excellent antibacterial property, hydrophobicity and antibacterial persistence, but also has low requirements for environmental illumination, has good antibacterial performance under visible light and dark environments, can be widely used in the field of functional coatings, and has good application value; in addition, the preparation method of the invention is economical and practical, has a simple preparation process, is low in cost, is easy to obtain raw materials, uses abundant sources of wormwood extract, is eco-friendly, does not require special equipment and harsh conditions, is easy to achieve large-scale production, and has extremely strong industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a picture of the wormwood-modified nano zinc oxide prepared in Example 1 of the present invention;

[0056] Figure 2 This is an infrared spectrum of the wormwood-coupled modified nano zinc oxide prepared in Example 1 of the present invention;

[0057] Figure 3 This is a water contact angle diagram of the hydrophobic antibacterial particles prepared in Example 1 of the present invention;

[0058] Figure 4 The hydrophobic antibacterial particles prepared in Example 1 of the present invention and the comparative hydrophobic antibacterial particles prepared in Comparative Examples 1-3 show the number of colonies of Staphylococcus aureus after seven days of use;

[0059] Figure 5 The anti-Staphylococcus aureus colony diagram of the hydrophobic antibacterial particle-containing real stone paint coating prepared in Example 1 of the present invention, and the comparative real stone paint coating prepared in Comparative Example 1 and Comparative Example 3 under dark environment and visible light irradiation environment;

[0060] Figure 6 This is a water contact angle diagram of the comparative hydrophobic antibacterial particles prepared in Comparative Example 1 of the present invention;

[0061] Figure 7 Schematic diagram of the preparation of the tangerine peel extract used in Comparative Example 5 of the present invention, FIG. a) is a picture of tangerine peel immersed in an ethanol aqueous solution; FIG. b) is a picture of the prepared tangerine peel extract;

[0062] Figure 8 This is a picture of orange peel modified nano zinc oxide prepared in Comparative Example 5 of the present invention;

[0063] Fig. 9 The arginine-modified polyurea emulsion prepared in Comparative Example 6 of the present invention and the polylysine-modified polyurea emulsion prepared in Example 1 are coated on tinplate sheets and dried to form a coated plate, which is then taken out after being immersed in water, wherein a) is an arginine-modified polyurea emulsion coated plate, and b) is a polylysine-modified polyurea emulsion coated plate;

[0064] Fig.10 The figures are of coating films of the arginine-modified polyurea emulsion prepared in Comparative Example 6 of the present invention and the polylysine-modified polyurea emulsion prepared in Example 1 immersed in water, wherein a) is the coating film of the arginine-modified polyurea emulsion, and b) is the coating film of the polylysine-modified polyurea emulsion. DETAILED DESCRIPTION

[0065] The technical scheme of the present invention is further described in detail and completely below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0066] Example 1

[0067] 1. Preparation of hydrophobic antibacterial particles

[0068] a) soaking 5 g of dried wormwood in 45 g of a 60 wt% ethanol aqueous solution at 70 ° C for 30 minutes, and filtering to obtain a wormwood extract for standby use;

[0069] 4.3902 g of zinc acetate dihydrate was added to 20 g of deionized water, and magnetic stirring was performed for 30 minutes to fully dissolve the zinc acetate dihydrate in the deionized water. Then, 2 g of ammonia water and 5 g of wormwood extract were added dropwise thereto respectively. After the addition was completed, the mixture was stirred at room temperature for 3 hours (stirring speed was 300 rpm). After the reaction was completed, the reaction solution was vacuum filtered, and the obtained filter cake was washed with anhydrous ethanol and deionized water respectively, and then dried at 125°C for 7 hours to obtain wormwood-modified nano zinc oxide.

[0070] b) taking 1 g of the wormwood-modified nano zinc oxide obtained in step a), adding it to 30 g of ethanol, and ultrasonically dispersing it for 30 minutes to uniformly disperse the wormwood-modified nano zinc oxide in the ethanol, and then adding 5 g of silane coupling agent KH570 and 10 g of deionized water thereto, stirring the resulting mixture at 85° C. for 1 hour (stirring speed is 350 rpm), after the reaction is completed, cooling the reaction solution to room temperature and centrifuging, washing the separated precipitate with ethanol (to remove excess water and oily substances) and filtering, and drying the filtered product at 80° C. for 8 hours to obtain powdered wormwood-coupled modified nano zinc oxide;

[0071] c) 3.5 g of isophorone diisocyanate was added to the reactor, and 10.5 g of polyetheramine D2000 was added dropwise at 40°C. After the addition was completed, the mixture was stirred and reacted for 2.5 hours (stirring speed was 200 rpm); then the temperature was raised to 80°C, and 0.47 g of 2,2-bis(hydroxymethyl)butyric acid, add, heat and stir for 1 hour (stirring speed is 205rpm); then keep the temperature at 80℃, add 0.08gε-polylysine, add, heat and stir for 1.5 hours; then cool to 70℃, add 0.14g trimethylolpropane, add, heat and stir for 1 hour; continue to cool to 50℃, add 0.38g triethylamine, add, heat and stir for 15 minutes; finally cool to 35℃, add 20g deionized water (to emulsify the prepolymer), add, heat and stir for 0.5 hour (stirring speed is 500rpm), and obtain polylysine modified polyurea emulsion;

[0072] d) adding 0.204 g of sodium alginate and 0.204 g of gelatin into 20 ml of deionized water, and stirring the mixture at 60° C. for 5 hours to obtain a sodium alginate-gelatin solution;

[0073] e) stirring 0.18 g of the polylysine-modified polyurea emulsion of step c) and 20 g of the sodium alginate-gelatin solution of step d) at room temperature for 40 minutes to mix the two uniformly (stirring speed is 500 rpm) to obtain a composite emulsion;

[0074] f) The composite emulsion is uniformly sprayed onto the surface of the wormwood-coupled modified nano zinc oxide at a uniform spray speed of 20 ml / min, and shaken evenly to allow the composite emulsion to be wrapped by the wormwood-coupled modified nano zinc oxide to form spherical particles. The spherical particles are added to 20 g of a 5% calcium chloride aqueous solution, and the resulting mixture is cross-linked at room temperature for 1.5 hours. The reaction is terminated, and the resulting reactant is freeze-dried under vacuum to a constant weight (freezing temperature is -40°C, freezing time is 24 hours), to obtain the hydrophobic antibacterial particles.

[0075] 2. Preparation of real stone paint containing hydrophobic antibacterial particles

[0076] Under the stirring speed of 600rpm, 65g natural colored sand, 2g hydrophobic antibacterial particles, 12g rutile titanium dioxide, 0.2g thickener hydroxyethyl cellulose ether, 0.25g defoamer Dow Corning DC-62, 0.35g BYK-180 wetting dispersant, and 0.2g dodecanol ester film-forming aid were added to 20g styrene acrylic resin in sequence, and stirred at room temperature for 50 minutes to mix the components evenly to obtain real stone paint containing hydrophobic antibacterial particles.

[0077] Figure 1 is a picture of the wormwood-modified nano zinc oxide prepared in this embodiment; Figure 1 It can be seen that the prepared wormwood-modified nano zinc oxide is a light green powdery solid, and the color of the product is close to the color of wormwood, indicating that the wormwood extract has been successfully modified. In addition, the particles in the powdery solid are evenly distributed, and there is basically no agglomeration phenomenon.

[0078] Figure 2 The infrared spectrum of the wormwood-coupled modified nano zinc oxide prepared in this example is Figure 2 It can be seen that the prepared wormwood-coupled modified nano zinc oxide showed characteristic peaks of silane coupling agent, indicating that the modification of silane coupling agent in step b) was successful.

[0079] Figure 3 The water contact angle diagram of the hydrophobic antibacterial particles prepared in this embodiment is shown in FIG. Figure 3 It can be seen that the water contact angle of the prepared hydrophobic antibacterial particles is 119.5°, which has good hydrophobicity.

[0080] The antibacterial properties of the hydrophobic antibacterial particles and the real stone paint containing the hydrophobic antibacterial particles prepared in this embodiment were tested, and the test method is as follows:

[0081] 1) Antibacterial performance test of hydrophobic antibacterial particles

[0082] Referring to WS / T650-2019 "Evaluation Method for Antibacterial and Antibacterial Effects", the hydrophobic antibacterial particles were mixed with bacteria at a concentration of 10 5 The bacterial concentration was observed after co-culturing the Staphylococcus aureus suspension for 1, 3, and 7 days, and the antibacterial rate R and antibacterial persistence were evaluated. The antibacterial rate R was calculated as follows:

[0083] R (%) = (BC) / B × 100

[0084] Wherein: R is the antibacterial rate (%) of the hydrophobic antibacterial particle sample; B is the average number of colonies recovered in the blank control sample within 24 hours (CFU / mL); C is the average number of colonies recovered in the hydrophobic antibacterial particle sample within 24 hours (CFU / mL).

[0085] The test results are shown in Table 1 and Figure 4 shown.

[0086] 2) Antibacterial performance test of real stone paint containing hydrophobic antibacterial particles

[0087] With reference to GB / T 30706-2014 "Test method and evaluation of antibacterial performance of photocatalytic antibacterial materials and products under visible light irradiation" and GB / T 21866-2008 "Determination of antibacterial activity and antibacterial effect of antibacterial coatings (paint films)", Staphylococcus aureus was used as the inoculated bacteria to determine the antibacterial activity of real stone paint containing hydrophobic antibacterial particles. A hydrophobic antibacterial particle real stone paint coating with a thickness of 2 mm was prepared using a film scraping frame. The dried coating was cut into a paint film plate of 50 mm × 50 mm in size for antibacterial testing. 0.4 mL of 10 5 The antibacterial rate of the sample was calculated by measuring the number of bacteria on the surface of the coating at 37°C for 24 hours and then the antibacterial rate R of the sample was calculated. 总 and photocatalytic antibacterial rate R 光 .

[0088] R 总 (%) = (C0-C1) / C0×100; R 光 (%) = (B1-C1) / B1×100

[0089] Where: R 总 , R 光 They are the antibacterial rate of the test sample and the antibacterial rate of the test sample under visible light irradiation (%); C0 is the viable bacterial count of the control sample after culture under light environment (CFU / piece); C1 is the viable bacterial count of the photocatalytic sample after culture under light environment (CFU / piece); B1 is the viable bacterial count of the photocatalytic sample after culture under dark environment (CFU / piece).

[0090] The test results are shown in Table 2 and Figure 5 shown.

[0091] Example 2

[0092] 1. Preparation of hydrophobic antibacterial particles

[0093] a) soaking 10 g of dried wormwood in 90 g of 70 wt% ethanol aqueous solution at 65 ° C for 45 minutes, and filtering to obtain a wormwood extract for standby use;

[0094] 8.7804 g of zinc acetate dihydrate was added to 40 g of deionized water, and magnetic stirring was performed for 45 minutes to fully dissolve the zinc acetate dihydrate in the deionized water. Then, 3 g of ammonia water and 3 g of wormwood leaf extract were added dropwise thereto respectively. After the addition was completed, the mixture was stirred at room temperature for 4 hours (stirring speed was 450 rpm). After the reaction was completed, the reaction solution was vacuum filtered, and the obtained filter cake was washed with anhydrous ethanol and deionized water respectively, and then dried at 100° C. for 9 hours to obtain wormwood-modified nano zinc oxide;

[0095] b) taking 2 g of the wormwood-modified nano zinc oxide obtained in step a), adding it to 60 g of ethanol, and ultrasonically dispersing it for 40 minutes to uniformly disperse the wormwood-modified nano zinc oxide in the ethanol, and then adding 10 g of silane coupling agent KH570 and 20 g of deionized water thereto, and stirring the resulting mixture at 80° C. for 2 hours (stirring speed is 400 rpm). After the reaction is completed, the reaction solution is cooled to room temperature and centrifuged, and the separated precipitate is washed with ethanol (to remove excess water and oily substances) and filtered. The filtered product is dried at 70° C. for 11 hours to obtain powdered wormwood-coupled modified nano zinc oxide;

[0096] c) 7g of isophorone diisocyanate was added to the reactor, 21g of polyetheramine D2000 was added dropwise at 45°C, and the mixture was stirred and reacted for 2 hours (stirring speed was 195 rpm); then the temperature was raised to 85°C, 0.94g of dimethylolpropionic acid was added, and the mixture was stirred and reacted for 1 hour (stirring speed was 180 rpm); then the temperature was kept constant at 80°C, 0.16g of ε-polylysine was added, and the mixture was stirred and reacted for 1.5 hours; then the temperature was lowered to 75°C, 0.28g of trimethylolpropane was added, and the mixture was stirred and reacted for 0.5 hour; the temperature was further lowered to 50°C, 0.76g of dimethylethanolamine was added, and the mixture was stirred and reacted for 20 minutes; finally, the temperature was lowered to 35°C, 40g of deionized water (to emulsify the prepolymer) was added dropwise, and the mixture was stirred and reacted for 1 hour (stirring speed was 700 rpm) to obtain a polylysine-modified polyurea emulsion;

[0097] d) adding 0.408 g of sodium alginate and 0.408 g of gelatin into 20 ml of deionized water, and stirring the mixture at 65° C. for 5 hours to obtain a sodium alginate-gelatin solution;

[0098] e) stirring 0.12 g of the polylysine-modified polyurea emulsion of step c) and 20 g of the sodium alginate-gelatin solution of step d) at room temperature for 45 minutes to uniformly mix the two (stirring speed is 550 rpm) to obtain a composite emulsion;

[0099] f) The composite emulsion is evenly sprayed onto the surface of the wormwood-coupled modified nano zinc oxide at a uniform spray speed of 100 ml / min, and shaken evenly to allow the composite emulsion to be wrapped by the wormwood-coupled modified nano zinc oxide to form spherical particles. The spherical particles are added to 30 g of a 4% calcium chloride aqueous solution, and the resulting mixture is cross-linked at room temperature for 1 hour. The reaction is terminated, and the resulting reactant is freeze-dried under vacuum to a constant weight (freezing temperature is -20°C, freezing time is 72 hours), to obtain the hydrophobic antibacterial particles.

[0100] 2. Preparation of real stone paint containing hydrophobic antibacterial particles

[0101] Under the stirring speed of 700rpm, 65g quartz sand, 4g hydrophobic antibacterial particles, 10g rutile titanium dioxide, 0.2 polyacrylate thickener, 0.25g polyether siloxane defoamer, 0.35g BYK-180 wetting and dispersing agent, and 0.2g propylene glycol film-forming aid were added to 20g acetic acid propylene resin in sequence, and stirred at room temperature for 40 minutes to mix the components evenly to obtain real stone paint containing hydrophobic antibacterial particles.

[0102] The antibacterial performance of the hydrophobic antibacterial particles and the real stone paint containing the hydrophobic antibacterial particles prepared in this embodiment was tested. The testing method was the same as that described in Example 1. The antibacterial performance test results of the hydrophobic antibacterial particles are shown in Table 1, and the antibacterial performance test results of the real stone paint containing the hydrophobic antibacterial particles are shown in Table 2.

[0103] Example 3

[0104] 1. Preparation of hydrophobic antibacterial particles

[0105] a) soaking 10 g of dried wormwood in 90 g of a 65 wt % ethanol aqueous solution at 60 ° C for 50 minutes, and filtering to obtain a wormwood extract for standby use;

[0106] 8.7804 g of zinc acetate dihydrate was added to 40 g of deionized water, and magnetic stirring was performed for 40 minutes to fully dissolve the zinc acetate dihydrate in the deionized water. Then, 2 g of ammonia water and 5 g of wormwood extract were added dropwise thereto respectively. After the addition was completed, the mixture was stirred at room temperature for 5 hours (stirring speed was 250 rpm). After the reaction was completed, the reaction solution was vacuum filtered, and the obtained filter cake was washed with anhydrous ethanol and deionized water respectively, and then dried at 80°C for 12 hours to obtain wormwood-modified nano zinc oxide;

[0107] b) taking 1.5 g of the wormwood-modified nano zinc oxide obtained in step a), adding it to 45 g of ethanol, and ultrasonically dispersing it for 30 minutes to uniformly disperse the wormwood-modified nano zinc oxide in the ethanol, and then adding 7.5 g of silane coupling agent KH570 and 15 g of deionized water thereto, and stirring the resulting mixture at 85° C. for 3 hours (stirring speed is 390 rpm). After the reaction is completed, the reaction solution is cooled to room temperature and centrifuged, and the separated precipitate is washed with ethanol (to remove excess water and oily substances) and filtered. The filtered product is dried at 75° C. for 9 hours to obtain a powdered wormwood-coupled modified nano zinc oxide;

[0108] c) 7g of isophorone diisocyanate was added to the reactor, 21g of polyetheramine ED900 was added dropwise at 45°C, and the mixture was stirred and reacted for 2 hours (stirring speed was 195 rpm); then the temperature was raised to 85°C, 0.94g of dimethylolpropionic acid was added, and the mixture was stirred and reacted for 1.5 hours (stirring speed was 215 rpm); then the temperature was kept constant at 85°C, 0.16g of α-polylysine was added, and the mixture was stirred and reacted for 1 hour; then the temperature was lowered to 70°C, 0.28g of trimethylolpropane was added, and the mixture was stirred and reacted for 1 hour; the temperature was further lowered to 50°C, 0.76g of dimethylethanolamine was added, and the mixture was stirred and reacted for 15 minutes; finally, the temperature was lowered to 30°C, 40g of deionized water (to emulsify the prepolymer) was added dropwise, and the mixture was stirred and reacted for 1.5 hours (stirring speed was 600 rpm) to obtain a polylysine-modified polyurea emulsion;

[0109] d) adding 0.816 g of sodium alginate and 0.816 g of gelatin into 20 ml of deionized water, and stirring the mixture at 70° C. for 6 hours to obtain a sodium alginate-gelatin solution;

[0110] e) stirring 0.18 g of the polylysine-modified polyurea emulsion of step c) and 20 g of the sodium alginate-gelatin solution of step d) at room temperature for 35 minutes to mix the two uniformly (stirring speed is 600 rpm) to obtain a composite emulsion;

[0111] f) The composite emulsion is uniformly sprayed onto the surface of the wormwood-coupled modified nano zinc oxide at a uniform spray speed of 150 ml / min, and shaken evenly to allow the composite emulsion to be wrapped by the wormwood-coupled modified nano zinc oxide to form spherical particles. The spherical particles are added to 40 g of a 2.5% calcium chloride aqueous solution, and the resulting mixture is cross-linked at room temperature for 1 hour. The reaction is terminated, and the resulting reactant is freeze-dried under vacuum to a constant weight (freezing temperature is -35°C, freezing time is 48 hours), to obtain the hydrophobic antibacterial particles.

[0112] 2. Preparation of real stone paint containing hydrophobic antibacterial particles

[0113] Under the stirring speed of 800rpm, 65g of permanent dyed sand, 2g of hydrophobic antibacterial particles, 12g of rutile titanium dioxide, 0.2g of associative alkali swelling thickener, 0.25g of Dow Corning DC-62 defoamer, 0.35g of BYK-180 wetting and dispersing agent, and 0.2g of dodecyl alcohol ester film-forming aid were added in sequence to 20g of silicone acrylic resin, and stirred at room temperature for 30 minutes to mix the components evenly to obtain real stone paint containing hydrophobic antibacterial particles.

[0114] The antibacterial performance of the hydrophobic antibacterial particles and the real stone paint containing the hydrophobic antibacterial particles prepared in this embodiment was tested. The testing method was the same as that described in Example 1. The antibacterial performance test results of the hydrophobic antibacterial particles are shown in Table 1, and the antibacterial performance test results of the real stone paint containing the hydrophobic antibacterial particles are shown in Table 2.

[0115] Comparative Example 1

[0116] The difference between this comparative example and Example 1 is that no wormwood extract is added in the preparation process of nano zinc oxide in step a), and the rest of the contents are the same as those described in Example 1. The specific preparation process is as follows:

[0117] 1. Preparation of comparative hydrophobic antibacterial particles

[0118] a) adding 4.3902 g of zinc acetate dihydrate to 20 g of deionized water and magnetically stirring for 30 minutes, gradually adding 3 g of ammonia water dropwise thereto, maintaining the rotation speed at 300 rpm, and continuing magnetic stirring for 3 hours, vacuum filtering the reaction precipitate, washing the filter cake with anhydrous ethanol and deionized water, and drying at 125° C. for 7 hours to obtain nano zinc oxide;

[0119] b) taking 1 g of the nano zinc oxide obtained in step a), adding it to 30 g of ethanol, and ultrasonically dispersing for 30 minutes to uniformly disperse the nano zinc oxide in the ethanol, and then adding 5 g of silane coupling agent KH570 and 10 g of deionized water thereto, stirring the resulting mixture at 85° C. for 1 hour (stirring speed is 350 rpm), after the reaction is completed, cooling the reaction solution to room temperature and centrifuging, washing the separated precipitate with ethanol (to remove excess water and oily substances) and filtering, and drying the filtered product at 80° C. for 8 hours to obtain coupled modified nano zinc oxide;

[0120] c) as described in Example 1;

[0121] d) as described in Example 1;

[0122] e) as described in Example 1;

[0123] f) The composite emulsion is uniformly sprayed onto the surface of the wormwood-coupled modified nano zinc oxide at a uniform spray speed of 20 ml / min, and shaken evenly to allow the composite emulsion to be wrapped by the wormwood-coupled modified nano zinc oxide to form spherical particles. The spherical particles are added to 20 g of a 5% mass concentration of calcium chloride aqueous solution, and the resulting mixture is cross-linked at room temperature for 1.5 hours. The reaction is terminated, and the resulting reactant is freeze-dried under vacuum to a constant weight (freezing temperature is -40°C, freezing time is 24 hours) to obtain comparative hydrophobic antibacterial particles.

[0124] 2. Comparison of the preparation of real stone paint

[0125] Under the stirring speed of 600rpm, 65g natural colored sand, 2g comparison hydrophobic antibacterial particles, 12g rutile titanium dioxide, 0.2g thickener hydroxyethyl cellulose ether, 0.25g defoamer Dow Corning DC-62, 0.35g BYK-180 wetting and dispersing agent, and 0.2g dodecanol ester film-forming aid were added to 20g styrene acrylic resin in sequence, and stirred at room temperature for 50 minutes to mix the components evenly to obtain a comparison real stone paint.

[0126] Figure 6 The water contact angle diagram of the comparative hydrophobic antibacterial particles prepared in this comparative example is shown in FIG. Figure 6 It can be seen that the water contact angle of the prepared comparative hydrophobic antibacterial particles is 98.1°, which is much smaller than the water contact angle of 119.5° of the hydrophobic antibacterial particles prepared in Example 1, indicating that the hydrophobicity of the comparative hydrophobic antibacterial particles prepared in this example is worse than that of the hydrophobic antibacterial particles prepared in Example 1. It can be seen that during the preparation of the antibacterial particles, the modification of the wormwood extract has a great influence on the hydrophobicity of the antibacterial particles.

[0127] The antibacterial performance test of the comparative hydrophobic antibacterial particles and the comparative real stone paint prepared in this comparative example was carried out. The test method was the same as that described in Example 1. The antibacterial performance test results of the comparative hydrophobic antibacterial particles are shown in Tables 1 and Figure 4 As shown in Table 2 and Table 3, the antibacterial performance test results of real stone paint are compared. Figure 5 shown.

[0128] Comparative Example 2

[0129] The difference between this comparative example and Example 2 is that in the preparation process of wormwood-coupling modified nano zinc oxide, wormwood and coupling modification are one-pot modifications, and the silane coupling agent KH570 used in the coupling modification is added to the reaction solution after wormwood modification in step a), and the rest of the contents are the same as those described in Example 1. The specific preparation process is as follows:

[0130] 1. Preparation of comparative hydrophobic antibacterial particles

[0131] a) soaking 10 g of dried wormwood in 90 g of 70 wt% ethanol aqueous solution at 65 ° C for 45 minutes, and filtering to obtain a wormwood extract for standby use;

[0132] 8.7804 g of zinc acetate dihydrate was added to 40 g of deionized water, and magnetic stirring was performed for 45 minutes to fully dissolve the zinc acetate dihydrate in the deionized water. Then, 3 g of ammonia water and 3 g of wormwood leaf extract were added dropwise thereto respectively. After the addition was completed, the mixture was stirred at room temperature for 4 hours (stirring speed was 450 rpm) to obtain a green solution containing wormwood-modified nano zinc oxide, which was set aside.

[0133] b) adding 60 g of ethanol to the green solution containing wormwood-modified nano zinc oxide obtained in step a), ultrasonically dispersing for 40 minutes, then adding 10 g of silane coupling agent KH570 and 20 g of deionized water to the obtained mixed solution, stirring the obtained mixture at 80° C. for 2 hours (stirring speed is 400 rpm), after the reaction is completed, cooling the reaction solution to room temperature and centrifuging, washing the separated precipitate with ethanol (to remove excess water and oily substances) and filtering, and drying the filtered product at 70° C. for 11 hours to obtain a comparative wormwood-coupled modified nano zinc oxide;

[0134] c) as described in Example 2;

[0135] d) as described in Example 2;

[0136] e) as described in Example 2;

[0137] f) The composite emulsion is evenly sprayed onto the surface of the wormwood-coupled modified nano zinc oxide at a uniform spray speed of 100 ml / min, and shaken evenly to allow the composite emulsion to be wrapped by the wormwood-coupled modified nano zinc oxide to form spherical particles. The spherical particles are added to 30 g of a 4% calcium chloride aqueous solution, and the resulting mixture is cross-linked at room temperature for 1 hour. The reaction is terminated, and the resulting reactant is freeze-dried under vacuum to a constant weight (freezing temperature is -20°C, freezing time is 72 hours), thereby obtaining the comparative hydrophobic antibacterial particles.

[0138] 2. Comparison of the preparation of real stone paint

[0139] Under the stirring speed of 700rpm, 65g quartz sand, 4g comparison hydrophobic antibacterial particles, 10g rutile titanium dioxide, 0.2 polyacrylate thickener, 0.25g polyether siloxane defoamer, 0.35g BYK-180 wetting and dispersing agent, and 0.2g propylene glycol film-forming aid were added to 20g acetic acid propylene resin in sequence, and stirred at room temperature for 40 minutes to mix the components evenly to obtain a comparison real stone paint.

[0140] The antibacterial performance test of the comparative hydrophobic antibacterial particles and the comparative real stone paint prepared in this comparative example was carried out. The test method was the same as that described in Example 1. The antibacterial performance test results of the comparative hydrophobic antibacterial particles are shown in Tables 1 and Figure 4 The antibacterial performance test results of real stone paint are shown in Table 2.

[0141] Comparative Example 3

[0142] The difference between this comparative example and Example 3 is that no wormwood extract and no polylysine-modified polyurea emulsion are added in the preparation process of the hydrophobic antibacterial particles. The rest of the contents are the same as those described in Example 3. The specific preparation process is as follows:

[0143] 1. Preparation of comparative hydrophobic antibacterial particles

[0144] a) 8.7804 g of zinc acetate dihydrate was added to 40 g of deionized water, and magnetic stirring was performed for 40 minutes to fully dissolve the zinc acetate dihydrate in the deionized water, and then 3 g of ammonia water was added dropwise thereto. After the addition was completed, the mixture was stirred at room temperature for 5 hours (stirring speed was 250 rpm). After the reaction was completed, the reaction solution was vacuum filtered, and the obtained filter cake was washed with anhydrous ethanol and deionized water, respectively, and then dried at 80° C. for 12 hours to obtain nano zinc oxide;

[0145] b) taking 1.5 g of the nano zinc oxide obtained in step a), adding it to 45 g of ethanol, and ultrasonically dispersing it for 30 minutes to uniformly disperse the wormwood-modified nano zinc oxide in the ethanol, and then adding 7.5 g of silane coupling agent KH570 and 15 g of deionized water thereto, stirring the resulting mixture at 85° C. for 3 hours (stirring speed is 390 rpm), after the reaction is completed, cooling the reaction solution to room temperature and centrifuging, washing the separated precipitate with ethanol (to remove excess water and oily substances) and filtering, and drying the filtered product at 75° C. for 9 hours to obtain coupled modified nano zinc oxide;

[0146] c) adding 0.816 g of sodium alginate and 0.816 g of gelatin into 20 ml of deionized water, and stirring the mixture at 70° C. for 6 hours to obtain a sodium alginate-gelatin solution;

[0147] d) The sodium alginate-gelatin solution was uniformly sprayed onto the surface of the wormwood-coupled modified nano zinc oxide at a uniform spray speed of 150 ml / min, and shaken evenly to allow the composite emulsion to be wrapped by the wormwood-coupled modified nano zinc oxide to form spherical particles. The spherical particles were added to 40 g of a 2.5% mass concentration of calcium chloride aqueous solution, and the resulting mixture was cross-linked at room temperature for 1 hour. The reaction was terminated, and the resulting reactant was freeze-dried under vacuum to a constant weight (freezing temperature of -35°C, freezing time of 48 hours), to obtain comparative hydrophobic antibacterial particles.

[0148] 2. Comparison of the preparation of real stone paint

[0149] Under the stirring speed of 800rpm, 65g of permanent dyed sand, 2g of comparison hydrophobic antibacterial particles, 12g of rutile titanium dioxide, 0.2g of associative alkali swelling thickener, 0.25g of Dow Corning DC-62 defoamer, 0.35g of BYK-180 wetting and dispersing agent, and 0.2g of dodecyl alcohol ester film-forming aid were added in sequence to 20g of silicone acrylic resin, and stirred at room temperature for 30 minutes to mix the components evenly to obtain a comparison real stone paint.

[0150] The antibacterial performance test of the comparative hydrophobic antibacterial particles and the comparative real stone paint prepared in this comparative example was carried out. The test method was the same as that described in Example 1. The antibacterial performance test results of the comparative hydrophobic antibacterial particles are shown in Tables 1 and Figure 4 As shown in Table 2 and Table 3, the antibacterial performance test results of real stone paint are compared. Figure 5 shown.

[0151] Comparative Example 4

[0152] The difference between this comparative example and Example 1 is that in step f), the composite emulsion is added dropwise onto the surface of the wormwood-coupled modified nano zinc oxide by a dropper, and the rest of the contents are the same as those described in Example 1. The specific preparation process is as follows:

[0153] 1. Preparation of comparative hydrophobic antibacterial particles

[0154] a) as described in Example 1;

[0155] b) as described in Example 1;

[0156] c) as described in Example 1;

[0157] d) as described in Example 1;

[0158] f) The composite emulsion is evenly added to the surface of the wormwood-coupled modified nano zinc oxide by a dropper, and shaken evenly to allow the composite emulsion to be wrapped by the wormwood-coupled modified nano zinc oxide to form spherical particles. The spherical particles are added to 20 g of a 5% calcium chloride aqueous solution, and the resulting mixture is cross-linked at room temperature for 1.5 hours. The reaction is terminated, and the resulting reactant is freeze-dried under vacuum to a constant weight (freezing temperature is -40°C, freezing time is 24 hours), to obtain comparative hydrophobic antibacterial particles.

[0159] 2. Comparison of the preparation of real stone paint

[0160] Under the stirring speed of 600rpm, 65g natural colored sand, 2g comparison hydrophobic antibacterial particles, 12g rutile titanium dioxide, 0.2g thickener hydroxyethyl cellulose ether, 0.25g defoamer Dow Corning DC-62, 0.35g BYK-180 wetting and dispersing agent, and 0.2g dodecanol ester film-forming aid were added to 20g styrene acrylic resin in sequence, and stirred at room temperature for 50 minutes to mix the components evenly to obtain a comparison real stone paint.

[0161] The antibacterial performance test of the comparative hydrophobic antibacterial particles and the comparative real stone paint prepared in this comparative example was carried out. The test method was the same as described in Example 1. The antibacterial performance test results of the comparative hydrophobic antibacterial particles are shown in Table 1, and the antibacterial performance test results of the comparative real stone paint are shown in Table 2.

[0162] Comparative Example 5

[0163] In this comparative example, orange peel extract was used instead of wormwood extract to modify zinc oxide, as follows:

[0164] Soak 5 g of orange peel in 45 g of 60 wt% ethanol aqueous solution at 70° C. for 30 minutes. After the soaking, filter to obtain an orange peel extract for later use.

[0165] 4.3902 g of zinc acetate dihydrate was added to 20 g of deionized water, and magnetic stirring was performed for 30 minutes to fully dissolve the zinc acetate dihydrate in the deionized water. Then, 2 g of ammonia water and 5 g of orange peel extract were added dropwise thereto respectively. After the addition was completed, the reaction was stirred at room temperature for 3 hours (stirring speed was 300 rpm). After the reaction was completed, the reaction solution was vacuum filtered, and the obtained filter cake was washed with anhydrous ethanol and deionized water respectively, and then dried at 125° C. for 7 hours to obtain orange peel modified nano zinc oxide;

[0166] Figure 7 Schematic diagram of the preparation of the orange peel extract used in this comparative example, FIG a) is a picture of orange peel immersed in ethanol aqueous solution; FIG b) is a picture of the prepared orange peel extract; Figure 7 It can be seen that the orange peel extract used is orange.

[0167] Figure 8 is a picture of the orange peel modified zinc oxide prepared in this comparative example; Figure 8 It can be seen that the prepared orange peel modified zinc oxide is a black solid, and the black solid is granular, has lumps and is difficult to disperse, has a low yield, and is not suitable for the preparation of subsequent experiments.

[0168] Comparative Example 6

[0169] In the preparation process of the modified polyurea emulsion in this comparative example, arginine was used instead of polylysine to modify the polyurea emulsion, as follows:

[0170] 3.5g of isophorone diisocyanate was added to the reactor, and 10.5g of polyetheramine D2000 was added dropwise at 40°C. After the addition was completed, the mixture was stirred and reacted for 2.5 hours (stirring speed was 200rpm). Then the temperature was raised to 80°C, and 0.56g of 2,2-bis(hydroxymethyl)butyric acid, after addition, heat preservation and stirring for 2.5 hours (stirring speed is 205rpm); then keep the temperature at 80℃ unchanged, add 0.22g arginine, after addition, heat preservation and stirring for 1.5 hours; then cool to 70℃, add 0.14g trimethylolpropane, after addition, heat preservation and stirring for 1 hour; continue to cool to 50℃, add 0.51g triethylamine, after addition, heat preservation and stirring for 0.5 hour; finally keep 50℃ unchanged, add 20g deionized water (to emulsify the prepolymer), after addition, heat preservation and stirring for 0.5 hour (stirring speed is 500rpm), and obtain arginine modified polyurea emulsion;

[0171] The stability of the arginine-modified polyurea emulsion prepared in this comparative example and the polylysine-modified polyurea emulsion prepared in Example 1 was investigated, and the specific method is as follows:

[0172] 1) The arginine modified polyurea emulsion prepared in this comparative example and the polylysine modified polyurea emulsion prepared in Example 1 were coated on tinplate sheets respectively. After drying, the coated sheets were soaked in water and taken out. The coated sheets after being taken out were as follows: Fig. 9 As shown;

[0173] 2) The arginine modified polyurea emulsion prepared in this comparative example and the polylysine modified polyurea emulsion prepared in Example 1 were coated on a polytetrafluoroethylene plate, respectively. After drying, the coating film was peeled off the polytetrafluoroethylene plate and then cut into a film of 1×1 cm in size. The film was immersed in water. The results are as follows: Fig.10 shown.

[0174] Fig. 9 The arginine modified polyurea emulsion prepared in this comparative example and the polylysine modified polyurea emulsion prepared in Example 1 are coated on the tinplate sheet and dried to form a coated plate after being soaked in water and taken out, wherein a) is the arginine modified polyurea emulsion coated plate, b) is the polylysine modified polyurea emulsion coated plate, from Fig. 9 It can be seen that the polyurea emulsion coating plate modified by polylysine has basically no change, while the polyurea emulsion coating plate modified by arginine has serious bubbling phenomenon, which indicates that the film formed by the arginine modified polyurea emulsion has poor stability when exposed to water.

[0175] Fig.10 The coating films of the arginine-modified polyurea emulsion prepared in this comparative example and the polylysine-modified polyurea emulsion prepared in Example 1 are immersed in water, wherein a) is the coating film of the arginine-modified polyurea emulsion, and b) is the coating film of the polylysine-modified polyurea emulsion. Fig.10 It can be seen that the coating film of the arginine-modified polyurea emulsion turned white in water, indicating that the film formed by the arginine-modified polyurea has poor stability when exposed to water.

[0176] It can be seen that during the preparation of hydrophobic antibacterial particles, when the polyurea emulsion is modified, although arginine and polylysine both belong to amino acid substances, the modification effects are significantly different. The polylysine-modified polyurea emulsion has good water stability and is suitable for the subsequent preparation of real stone paint, while the arginine-modified polyurea emulsion has poor water stability and is not suitable for the subsequent preparation of real stone paint. This also shows that the modification effect of the polyurea emulsion modified by polylysine in the present invention is unpredictable.

[0177] Table 1 Test results of 7d antibacterial rate of hydrophobic antibacterial particles prepared in Examples 1-3 and Comparative Examples 1-3

[0178] Test samples 1d antibacterial rate R (%) 3d antibacterial rate R (%) 7d antibacterial rate R (%) Example 1 99.9 99.9 99.9 Example 2 99.8 99.7 99.7 Example 3 99.9 99.9 99.9 Comparative Example 1 75.2 73.4 71.1 Comparative Example 2 97.7 95.8 93.2 Comparative Example 3 48.3 47.4 43.6 Comparative Example 4 99.7 99.5 99.3

[0179] Table 2 Test results of total antibacterial rate and photocatalytic anti-Staphylococcus aureus rate of real stone paint coating containing hydrophobic antibacterial particles

[0180] Test samples <![CDATA[R 总 (%)]]> <![CDATA[R 光 (%)]]> Example 1 96.7 92.1 Example 2 98.4 94.6 Example 3 97.1 93.3 Comparative Example 1 73.3 13.1 Comparative Example 2 95.2 70.9 Comparative Example 3 32.1 3.1 Comparative Example 4 96.2 91.8

[0181] It can be seen from Table 1 and Table 2 that the method of the present invention (such as Examples 1-3) can obtain hydrophobic antibacterial particles with excellent antibacterial properties and real stone paint containing hydrophobic antibacterial particles, which have excellent antibacterial durability and visible light antibacterial effect on Staphylococcus aureus; and, compared with the case where no wormwood extract is added (Comparative Example 1) or wormwood and coupled modified nano zinc oxide are modified in one pot (Comparative Example 2) or polylysine-modified polyurea emulsion and wormwood extract are not added (Comparative Example 3), significant improvements are produced under the same conditions, which also shows that the technical scheme of synthesizing wormwood-modified zinc oxide through wormwood extract and modifying it with silane coupling agent KH570 after synthesis to obtain wormwood-coupled modified nano zinc oxide and adding polylysine-modified polyurea emulsion has a synergistic effect;

[0182] In addition, the total antibacterial rate and photocatalytic antibacterial rate of the real stone paint coating containing hydrophobic antibacterial particles prepared in Examples 1-3 are relatively excellent, and have good antibacterial rates in both visible light and dark environments. This is because it is adsorbed on the surface of sodium alginate-gelatin and polylysine-modified polyurea emulsions to reduce its loss, and it still has good antibacterial properties even after being used for a period of time;

[0183] In addition, among Examples 1-3, the real stone paint of Example 2, which has the highest content of hydrophobic antibacterial particles, has the best antibacterial effect, indicating that the content of hydrophobic antibacterial particles has a certain influence on the antibacterial effect of real stone paint;

[0184] In addition, the only difference between Comparative Example 4 and Example 1 is the different way of adding the composite emulsion, and the antibacterial properties of the hydrophobic antibacterial particles and the real stone paint coating containing hydrophobic antibacterial particles prepared in Example 1 are slightly better than those of Comparative Example 4, indicating that the way of adding the composite emulsion has a certain influence on the antibacterial properties of the hydrophobic antibacterial particles and the real stone paint coating containing hydrophobic antibacterial particles.

[0185] Finally, it should be pointed out that the above are only some preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above contents of the present invention all fall within the scope of protection of the present invention.

Claims

1. A hydrophobic antibacterial particle, characterized in that: First, polylysine-modified polyurea emulsion is compounded with sodium alginate-gelatin solution to obtain a composite emulsion, and then the composite emulsion is wrapped by wormwood-coupled modified nano zinc oxide to form spherical particles, and then the spherical particles are cross-linked with calcium chloride to obtain the wormwood-coupled modified nano zinc oxide; the wormwood-coupled modified nano zinc oxide is obtained by modifying zinc oxide with wormwood extract and silane coupling agent in sequence.

2. A method for preparing the hydrophobic antibacterial particles according to claim 1, characterized in that: The steps include: a) dissolving zinc acetate dihydrate in deionized water, then dropping ammonia water and wormwood extract therein, stirring at room temperature for 3 to 5 hours, collecting the solid product, and obtaining wormwood-modified nano zinc oxide; b) dispersing the wormwood-modified nano zinc oxide in ethanol, then adding a silane coupling agent and deionized water thereto, stirring the resulting mixture at 75 to 85° C. for 1 to 3 hours, collecting a solid product, and obtaining wormwood-coupled modified nano zinc oxide; c) adding isocyanate to a reactor, adding polyetheramine dropwise at 40-45° C., and reacting with stirring at the temperature for 2-2.5 hours; then raising the temperature to 80-85° C., adding a hydrophilic chain extender, and reacting with stirring at the temperature for 1-1.5 hours; then keeping the temperature at 80-85° C. unchanged, adding polylysine, and reacting with stirring at the temperature for 1-1.5 hours; then cooling to 70-75° C., adding a crosslinking agent, and reacting with stirring at the temperature for 0.5-1 hour; further cooling to 45-50° C., adding a neutralizing agent, and reacting with stirring at the temperature for 15-30 minutes; finally cooling to 30-35° C., adding deionized water dropwise, and reacting with stirring at the temperature for 0.5-1.5 hours to obtain a polylysine-modified polyurea emulsion; d) adding equal amounts of sodium alginate and gelatin into deionized water, and stirring the mixture at 60 to 70° C. for 5 to 6 hours to obtain a sodium alginate-gelatin solution; e) mixing the polylysine-modified polyurea emulsion of step c) and the sodium alginate-gelatin solution of step d) at room temperature to obtain a composite emulsion; f) adding the composite emulsion evenly to the surface of the wormwood-coupled modified nano zinc oxide, shaking evenly to allow the composite emulsion to be wrapped by the wormwood-coupled modified nano zinc oxide to form spherical particles, adding the spherical particles to a calcium chloride aqueous solution, and subjecting the resulting mixture to a cross-linking reaction at room temperature for 1 to 3 hours, terminating the reaction, and freeze-drying the resulting reactant under vacuum to a constant weight to obtain the hydrophobic antibacterial particles.

3. The method according to claim 2, characterized in that In step a), the preparation of the wormwood leaf extract comprises the following operations: Soak the dried mugwort in a 60-70wt% ethanol aqueous solution at a temperature of 60-70°C for 30-60 minutes. After the soaking, filter and the filtrate is the mugwort extract. During the preparation of the mugwort extract, the added amounts of dry mugwort and 60-70wt% ethanol aqueous solution are: 5-10 parts by mass of dry mugwort and 40-90 parts by mass of 60-70wt% ethanol aqueous solution.

4. The method according to claim 2, characterized in that: In step a), the added amounts of zinc acetate dihydrate, deionized water, ammonia water and wormwood leaf extract are: 4-9 parts by mass of zinc acetate dihydrate, 20-40 parts by mass of deionized water, 2-5 parts by mass of ammonia water and 1-10 parts by mass of wormwood leaf extract.

5. The method according to claim 2, characterized in that: In step b), the silane coupling agent is any one of KH570, KH550, and KH560; in step b), the added amounts of wormwood-modified nano zinc oxide, ethanol, silane coupling agent, and deionized water are: 1 to 2 parts by mass of wormwood-modified nano zinc oxide, 30 to 60 parts by mass of ethanol, 5 to 20 parts by mass of silane coupling agent, and 10 to 20 parts by mass of deionized water.

6. The method according to claim 2, characterized in that: In step c), the isocyanate is any one of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, polymethylene polyphenyl polyisocyanate, and hexamethylene diisocyanate; the polyetheramine is any one of polyetheramine D2000, polyetheramine ED900, and polyetheramine D230; the hydrophilic chain extender is any one of 2,2-bis(hydroxymethyl)butyric acid, dimethylolpropionic acid, and dihydroxysulfonate; the polylysine is any one of ε-polylysine and α-polylysine; the cross-linking agent is any one of trimethylolpropane, 1,2-propylene glycol, and ethylene glycol; and the neutralizing agent is any one of triethylamine, dimethylethanolamine, and ammonia water.

7. The method according to claim 2, characterized in that: In step c), the added amounts of isocyanate, polyetheramine, hydrophilic chain extender, polylysine, crosslinking agent, neutralizer and deionized water are: 3.5-7 parts by mass of isocyanate, 10.5-21 parts by mass of polyetheramine, 0.28-0.56 parts by mass of hydrophilic chain extender, 0.1-0.28 parts by mass of polylysine, 0.14-0.28 parts by mass of crosslinking agent, 0.38-0.4 parts by mass of neutralizer and 20-40 parts by mass of deionized water; in step d), the mass concentration of the obtained sodium alginate-gelatin solution is 2%-6%; in step e), the added amounts of polylysine-modified polyurea emulsion and sodium alginate-gelatin solution in the composite emulsion are: 0.09-0.12 parts by mass of polylysine-modified polyurea emulsion and 15-20 parts by mass of sodium alginate-gelatin solution.

8. The method according to claim 2, characterized in that: In step f), the added amounts of wormwood-coupled modified nano zinc oxide and calcium chloride aqueous solution are: 0.2-0.4 parts by mass of wormwood-coupled modified nano zinc oxide and 20-40 parts by mass of calcium chloride aqueous solution, wherein the mass concentration of the calcium chloride aqueous solution is 2.5-5%.

9. A real stone paint containing hydrophobic antibacterial particles prepared by using the hydrophobic antibacterial particles according to claim 1, characterized in that: The real stone paint containing hydrophobic antibacterial particles has the following composition and proportion: Resin: 10-30 parts by mass; Colored sand: 50-70 parts by weight; Hydrophobic antibacterial particles: 0.1 to 5 parts by weight; Titanium dioxide: 5-15 parts by mass; Thickener: 0.2-0.5 parts by mass; Defoaming agent: 0.1-0.3 parts by mass; Wetting and dispersing agent: 0.2-0.6 parts by mass; Film-forming aid: 0.2-0.5 parts by weight.

10. A method for preparing the real stone paint containing hydrophobic antibacterial particles according to claim 9, characterized in that: The method comprises the following steps: adding colored sand, hydrophobic antibacterial particles, titanium dioxide, thickener, defoamer, wetting dispersant and film-forming aid to a proportion of resin in a stirring state, stirring and mixing evenly to obtain the real stone paint containing hydrophobic antibacterial particles.

Citation Information

Patent Citations

  • Nanometer ZnO anti-bacterial and anti-fouling coating and method for preparing same

    CN101701120A

  • Flame-retardant, antibacterial and acid and alkali resistant wall cloth and paper coating for interior decoration

    CN106085230A

  • Vegetable oil-based polyurea super-hydrophobic coating and preparation method thereof

    CN114702886A

  • Lysine-based polyurethane polyurea with spider silk-like secondary structure as well as preparation and application of lysine-based polyurethane polyurea

    CN116769129A

  • Methods and compositions for making an amino acid triisocyanate

    US20150197488A1

Cited By

  • Steel rod tailing ultra-high performance concrete pole and manufacturing method thereof

    CN120736832A